Financial development, human capital accumulation and economic growth: empirical evidence from the economic community of West African states - Abubakar, Abdulsalam; Kassim, Salina; Yusoff, Mohammed (2014)
From the perspective of the endogenous growth models, the poor economic performance of the ECOWAS region can be traced to the low level of human capital accumulation in the region. However, recently, great attention has been paid to the role of financial development towards economic growth, by encouraging capital accumulation. But capital in this sense referred to only physical capital. Therefore, this study differ from others by investigating the link between financial development, human capital accumulation and economic growth in the ECOWAS. It employed panel cointegration approaches as well as fully modified OLS and dynamic OLS estimators and panel granger causality test. The results revealed that bank private credit and domestic private credit contribute significantly to economic growth in the ECOWAS, both directly and through their influence on human capital accumulation. Moreover, whereas bank credit Granger cause economic growth, bidirectional causality exist between domestic credit and economic growth. These results imply that providing access to credit to both enterprises and individuals, through appropriate financial policies, will encourage economic growth in the ECOWAS region.